Radikálová syntéza nukleových bází z formamidu v impaktním plazmatu - Ferus, Martin; Knížek, Antonín; Šponer, Jiří; Šponer, Judit Erika; Civiš, Svatopluk (Chemické listy, 2015)
The end of the late heavy bombardment era coincides with the emergence of life on the Earth 4 billion years ago. This coincidence suggests that the impacts of extraterrestrial bodies might have contributed to the formation of the first molecules involved in early living structures. We have simulated a high-energy synthesis of nucleic acid bases from formamide in the impact of an extraterrestrial body. The high-power laser system PALS was employed in simulation of impact plasma by inducing a laser dielectric breakdown in formamide. In hot and dense plasma, formamide decomposed producing reactive radicals. The radicals reacted with formamide and nucleic acid bases were produced. Formamide was pretreated with laser plasma in the presence of catalysts. The products were analyzed by FTIR spectrometry and GC-MS. Time-resolved emission spectra of formamide discharge plasma were measured. Kinetic models and formation pathways for nucleic acid bases were calculated. The results show that the nucleic acid bases can be synthesized in impact plasma involving CN and NH radicals and formamide.
Keywords: Nucleic Acids; Earth, Planet; Lasers; Organelle Biogenesis; nukleové kyseliny; plynová chromatografie s hmotnostně spektrometrickou detekcí; Formamides; spektroskopie infračervená s Fourierovou transformací; Catalysis; formamidy; Spectroscopy, Fourier Transform Infrared; Gas Chromatography-Mass Spectrometry; lasery; katalýza; biogeneze organel; Země (planeta)